PROBLEMATIKA SUMBER BELAJAR PENDIDIKAN AGAMA HINDU DI SMPN 1 PERMATA KECUBUNG - Mardwiatmoko Mardwiatmoko Mardwiatmoko (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2023)
In Permata Kecubung Subdistrict or even in Sukamara Regency, educators and students encounter obstacles in obtaining learning resources, especially printed teaching materials, such as Vedic Scriptures, Modules, Hand Outs, LKPD, LKS, lesson companion books and so on. This research uses a qualitative approach with a narrative method. In this study the authors used field texts, such as stories, journals, field notes, letters, conversations, interviews, photos (and other artifacts), and personal experience, as an analysis unit to research and understand how the problems of learning resources and problem solving in learning Hindu Religious Education at SMP Negeri 1 Permata Kecubung. This study aims to describe the problems of learning resources and problem-solving strategies for Hindu Religious Education at SMP Negeri 1 Permata Kecubung. The results showed that the only available learning resources were teachers and package books without other printed teaching materials, the number of computer units in schools was inadequate. The problem-solving strategy carried out is for educators to develop printed teaching materials in the form of Student Worksheets (LKPD), teaching modules and prayer spell teaching materials as well as compiling learning media assisted by YouTube and Ms PowerPoint. Due to the limited number of computers, the school requested computer assistance from the Sukamara District Education and Culture Office.